1998
DOI: 10.1080/07315724.1998.10718735
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, Insulin and Diabetes

Abstract: The relationship between diabetes, insulin and zinc (Zn) is complex with no clear cause and effect relationships. In Type 1 diabetes there is a lack of insulin production, in Type 2 diabetes resistance to the effects of insulin are predominant. Both Type 1 and Type 2 have the same long-term complications. Diabetes effects zinc homeostasis in many ways, although it is most probably the hyperglycemia, rather than any primary lesion related to diabetes, which is responsible for the increased urinary loss and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
344
1
22

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 635 publications
(379 citation statements)
references
References 31 publications
12
344
1
22
Order By: Relevance
“…Therefore, DTZ staining is recognized as a valuable part of a possible approach to harvest human pancreatic islets from cadaveric donors as well as those with nonbeating hearts [30,31]. Zinc is required in pancreatic β cells for packaging insulin, an integral part of insulin crystals for 2-Zn-insulin hexamer, as well as free ionized zinc in the extragranular space that acts as a reservoir for granular zinc [42,43]. We took advantage of these zinc pools to identify cells harboring insulin-production ability Identification of Pancreatic Islets from ES Cells by DTZ that were in the mouse EB culture outgrowths and found emerging cellular clusters that were stained crimson red by DTZ in mixed populations of ES derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DTZ staining is recognized as a valuable part of a possible approach to harvest human pancreatic islets from cadaveric donors as well as those with nonbeating hearts [30,31]. Zinc is required in pancreatic β cells for packaging insulin, an integral part of insulin crystals for 2-Zn-insulin hexamer, as well as free ionized zinc in the extragranular space that acts as a reservoir for granular zinc [42,43]. We took advantage of these zinc pools to identify cells harboring insulin-production ability Identification of Pancreatic Islets from ES Cells by DTZ that were in the mouse EB culture outgrowths and found emerging cellular clusters that were stained crimson red by DTZ in mixed populations of ES derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…12 Some previous studies indicated that the lower serum zinc in diabetics may be due to diabetes related hyperzincuria and impaired gastrointestinal absorption of zinc. 13 In addition to the findings that zinc levels are often low in diabetic, it is also felt that zinc (along with other micronutrients) may participate as an integral component of antioxidant enzymes. Decrease in intracellular zinc and zinc dependent antioxidant enzyme lead to an increase in intracellular oxidant and free radicals-that associated with complications of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Zn also increases insulin sensitivity by increasing the 2567 sensitivity of insulin binding to its receptors. [2].Disordered metabolism of zinc may interfere with achievement of glycemic control in DM and in turn leads to development of complications.…”
Section: Discussion:-mentioning
confidence: 99%
“…Insulin resistance leads to increased visceral fat, dyslipidemia, hypertension, ,vasculopathy, increased platelet aggregation, endothelial dysfunction and accelerated atherosclerosis. [2] The altered metabolism of various minerals and trace elements has been implicated in diabetes mellitus and these elements may play a vital role in the itiopathogenesis and progression of the disease. Of these trace elements-magnesium, zinc and copper are important for various physiologic functions.…”
mentioning
confidence: 99%